Virulence factor profiles, phylogenetic background, and antimicrobial resistance pattern of lactose fermenting and nonlactose fermenting Escherichia coli from extraintestinal sources - Arindam Chakraborty; Prabha Adhikari; Shalini Shenoy; Vishwas Saralaya (Wolters Kluwer Medknow Publications, 2016)
Context: In recent years, nonlactose fermenting (NLF) Escherichia coli have been increasingly isolated in the microbiology laboratory, but their clinical significance has not yet been clearly elucidated. Aims: To characterize the lactose fermenting (LF) and NLF isolates on the basis of their virulence factors, phylogenetic background, and drug resistance property. Settings and Design: This descriptive study was carried out in a multi-specialty tertiary care hospital. Subjects and Methods: Three hundred nonrepeat E. coli isolates from inpatients were studied. Isolates were differentiated as LF and NLF on the basis of colony characteristics on MacConkey's agar. Possession of virulence and drug resistance genes was determined by multiplex polymerase chain reaction (PCR). Phylogenetic analysis was performed by triplex PCR methods. Antibiotic sensitivity testing was performed by disk diffusion method. Results: Of 300 isolates 39 (13%) were NLF isolates. Maximum number of NLF isolates belonged to phylogroups B2 and D when compared with LF isolates. The incidence of iutA, hlyA, and neuC genes were significantly higher in NLF isolates. The presence of drug resistance genes such as AmpC gene, SHV, and CTXM were higher in LF isolates. Conclusions: LF isolates demonstrated a higher antimicrobial resistance and NLF isolates possessed higher virulence properties. The microbiology laboratory should report lactose fermentation profile as it may help the physician to initiate appropriate treatment.